"Historical (f)actors: Environments and histories in modern North Africa". Issue 12 (31st October 2018) - Cutler, Brock
Abstract: Despite the rise in environmental thinking and environmental questions throughout the humanities—what some people call the "environmental turn"—environmental history has remained marginal to the field of North African history. This article explores the field of environmental history of North Africa in order to think through some potential ways to address this lacuna. The article does this by first providing a brief overview of the field of environmental history, with an emphasis on North Africa. It then turns to the broader trends in this area and highlights some recent scholarship before suggesting an alternative approach that might be useful to North Africanists and other scholars.